A cell-loss-free concave microwell array based size-controlled multi-cellular tumoroid generation for anti-cancer drug screening. - Sang Woo Lee; Soo Yeon Jeong; Tae Hoon Shin; Junhong Min; Donghyun Lee; Gi Seok Jeong (PLoS ONE, 2019)
The 3D multi-cellular tumoroid (MCT) model is an in vivo-like, avascular tumor model that has received much attention as a refined screening platform for drug therapies. Several types of research have been efforted to improve the physiological characteristics of the tumor microenvironment (TME) of the in vivo-like MCTs. Size-controlled MCTs have received much attention for obtaining highly reproducible results in drug screening assays and achieving a homogeneous and meaningful level of biological activities. Here, we describe an effective method for fabricating the size-controlled in vivo-like MCTs using a cell-loss-free (CLF) microwell arrays. The CLF microwell arrays was fabricated by using the simple operation of laser carving of a poly (methyl methacrylate) (PMMA) master mold. We also demonstrated the biophysicochemical effect of tumor microenvironment (TME) resident fibroblasts through the expression of TGFβ, αSMA, Type I-, IV collagen, angiogenesis related markers on tumorigenesis, and confirmed the drug response of MCTs with anti-cancer agents. This technology for the fabrication of CLF microwell arrays could be used as an effective method to produce an in vitro tumor model for cancer research and drug discovery.